Integrating Indigenous Practices into Environmental Monitoring - Leha, Saliman; Nor Hanim, Awang @ Mohd Noor; Wong, Swee Kiong (Journal of Chemical Health Risks (JCHR), 2024)
The integration of indigenous knowledge (IK) into environmental monitoring initiatives holds significant promise for fostering sustainable development and resource management. This study focuses on integrating Iban indigenous practices into environmental monitoring efforts in Sri Aman, Sarawak, emphasising the importance of incorporating local knowledge systems for effective environmental stewardship. The objective of this study is to assess the benefits of integrating Iban indigenous practices into contemporary environmental monitoring frameworks in Sri Aman, Sarawak. Results reveal a notable trend of diversification in livelihood activities among households, reflecting a holistic approach to enhancing livelihoods. Gender dynamics play a significant role in shaping livelihood strategies, with IK serving as a fundamental mechanism for mitigating livelihood vulnerabilities. Moreover, the pervasive utilisation of IK emerges as integral to sustaining livelihoods, particularly in agricultural practices. The integration of indigenous practices into environmental monitoring is identified as crucial for enhancing the efficacy of conservation and resource management initiatives and fostering more resilient and environmentally sustainable communities. The discussion highlights the intrinsic link between IK, livelihood sustainability, and environmental monitoring, emphasising the need to integrate IK into monitoring frameworks for holistic resource management. It also explores the importance of IK in non-farm livelihoods among the Iban communities, showcasing its influence on daily activities and choice of livelihood strategies beyond traditional agricultural practices. In conclusion, the integration of Iban indigenous practices into environmental monitoring represents a promising avenue for fostering sustainable development and environmental resilience in Sri Aman, Sarawak. Recognising and valuing indigenous knowledge systems enhances the effectiveness and inclusivity of environmental monitoring initiatives, contributing to the conservation and protection of natural resources for future generations.